1989
DOI: 10.1080/02772248909357366
|View full text |Cite
|
Sign up to set email alerts
|

Fate of anilines and related compounds in the environment. A review

Abstract: The environmental aspects of the fate of anilines and related compounds are examined. They include the ecotoxicological aspects, the physico-chemical and (bio)chemical reactions in the gas phase, aquatic environments, plants and soil. The particularity of this class of substances is the formation of "bound residues" in high quantities, up to 95% in soil within one vegetation period. Some new results on the catalytically induced incorporation of anilines in soil organic matter are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…This study accords with our earlier observations that showed difficult extraction of 3-CA from potato peel [25]. In reviewing the literature, several investigations have been reported on the fate of chloroaniline compounds in the plants indicating bound or nonextractable residues of these compounds [26][27][28].…”
Section: Introductionsupporting
confidence: 91%
“…This study accords with our earlier observations that showed difficult extraction of 3-CA from potato peel [25]. In reviewing the literature, several investigations have been reported on the fate of chloroaniline compounds in the plants indicating bound or nonextractable residues of these compounds [26][27][28].…”
Section: Introductionsupporting
confidence: 91%
“…In addition, natural humic acids affected bioconcentration (Steinberg et al, 1994a), bioavailability (Adrian et al, 1989;Alberts et al, 1992), and aquatic ecotoxicity . The behavior of fish exposed to the triazine terbuthylazine changed in the presence of aquatic humic substances (Steinberg et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…Aniline and its derivatives are involved in many industrial and agricultural processes and are often found in the environment [1]. These compounds can be toxic, mutagenic, or carcinogenic [5].…”
Section: Introductionmentioning
confidence: 99%